Mind wandering via mental contrasting as a tool for behavior change - Oettingen, Gabriele; Schwoerer, Bettina (Frontiers in Psychology, 2013)
When people engage in mind wandering they drift away from a task towards their inner thoughts and feelings. These thoughts often circle around people’s personal futures. One assumed function of mind wandering is that it aids problem solving and planning for the future. We will discuss different forms of mind wandering and their effects on problem solving and behavior change. While solely fantasizing about a desired future leads to poor problem solving and little behavior change, mind wandering in the form of mental contrasting leads to skilled problem solving and substantial behavior change. In mental contrasting, people first envision the desired future and then imagine the obstacles that need to be surmounted to reach said future. Mental contrasting instigates behavior change by modulating the strength of associations between future and reality and between reality and instrumental action. Intervention research shows that mental contrasting can be taught as a cost- and time-effective self-regulation strategy of behavior change. The findings have implications for research on mind wandering, problem solving, and on creating effective interventions of behavior change.